PEMBERDAYAAN PERPUSTAKAAN PESANTREN BERBASIS OTOMASI DAN DIGITAL - Muhammad Amir Mahmud (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2013)
Library is one means a place to get information.Today many libraries are still not maximized utilization. This is due to several factors, including the old paradigm that sees the library just as "barn book". Another factor is the lack of knowledge about good library management, lack of interest in reading, limited library collections, lack of facilities and supporting infrastructure, and so forth. The above conditions also appear in the library that are in boarding school. Although general awareness in Indonesian pesantren education institutions about the significance of libraries have started to grow, but generally the management of the boarding school libraries are still not maximized. Pondok Pesantren Darussalam, Blokagung, Tegalsari, Banyuwangi regency as the oldest boarding school inBanyuwangi and one of the largest in Banyuwangi, the number of students more than 5500 people, boarding can be a model for other boarding institution. To improve the quality and speed of access libraries library services should be conducted library training management and implementation of library services and materials based library automation and digital. The training given to the librarian about library management system followed by the application of library automation services. The result has been based on library services and digital automation systems that facilitate services to benefit the library and librarians, libraries and library users.